2015
DOI: 10.1038/srep10842
|View full text |Cite
|
Sign up to set email alerts
|

Novel Handheld Magnetometer Probe Based on Magnetic Tunnelling Junction Sensors for Intraoperative Sentinel Lymph Node Identification

Abstract: Using magnetic tunnelling junction sensors, a novel magnetometer probe for the identification of the sentinel lymph node using magnetic tracers was developed. Probe performance was characterised in vitro and validated in a preclinical swine model. Compared to conventional gamma probes, the magnetometer probe showed excellent spatial resolution of 4.0 mm, and the potential to detect as few as 5 μg of magnetic tracer. Due to the high sensitivity of the magnetometer, all first-tier nodes were identified in the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
32
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 21 publications
0
32
1
Order By: Relevance
“…The magnetometer probe is most effective when measuring nodes with tracer uptake concentrated close to the node surface where it can be measured at very close range. 28 However, in the present study, the SLNs showed a very heterogeneous SPION uptake. In vivo, adipose tissue surrounding SLNs can limit the distance of the probe to the node resulting in insufficient exposure of the node or not sufficient measurement of the magnetic signal.…”
contrasting
confidence: 65%
“…The magnetometer probe is most effective when measuring nodes with tracer uptake concentrated close to the node surface where it can be measured at very close range. 28 However, in the present study, the SLNs showed a very heterogeneous SPION uptake. In vivo, adipose tissue surrounding SLNs can limit the distance of the probe to the node resulting in insufficient exposure of the node or not sufficient measurement of the magnetic signal.…”
contrasting
confidence: 65%
“…An insufficient measurement of the magnetic signal can be the result. Moreover, the presence of tissue in the vicinity of the probe tip of the magnetometer and the LN reduces the in vivo magnetic signal because of the negative magnetic susceptibility of surrounding tissue [20]. The limited spatial resolution of the SentiMag ® probe (~20 mm) could restrain the differentiation of SLN signals from the background signal from the injection site.…”
Section: Discussionmentioning
confidence: 99%
“…The limited spatial resolution of the SentiMag ® probe (~20 mm) could restrain the differentiation of SLN signals from the background signal from the injection site. In the near future, the higher resolution of novel probes using magnetic tunneling junction techniques (resolution~4 mm) could lead to a sustainable improvement in intracorporeally SLN identification [20]. In addition, the now available possibility of preoperative localization of magnetically marked SLNs using magnetic resonance imaging (MRI) could further improve intraoperative detectability [10].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows such a magnetic transfer curve of a representative MTJ sample (MTJ-1). Within the field range of ±100 Oe, the magnetoresistance response is primarily from the free layer of 3-nm Co 40 Fe 40 B 20 . In our MTJ samples, the exchange-bias provides a pinning field of about 500 Oe for the SAF hard layer, which remains mostly inert within ±100 Oe.…”
mentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] Applications of MTJs have extended beyond read heads in hard disk drives and MRAMs. MTJ sensors have been used for medical and biological devices, 20 high frequency oscillators, 24 non-destructive testing, 25 current sensors, 26 and ultra-low noise sensors. 27 MTJ sensors due to its high sensitivity and thermal performance have becoming an enabling technology in many areas of science and engineering.…”
mentioning
confidence: 99%